Motivasi Berprestasi Siswa Kelas 3 Jurusan Tata Busana Di SMK Negeri 3 Sungai Penuh - MUSTIKA, SRI DEFI; k, yusmar emmy; izwerni, izwerni (Journal of Home Economics and Tourism, 2013)
This study aimed to determine the student achievement motivation  majoring infashion at SMK N 3 Sungai Penuh, achievement motivation can be seen from thestudents' expectations of success, the need for knowledge and skills of fashion. Thisresearch is included descriptive research, the student population in this study majoring infashion class 3 subjects SMK N 3 Sungai Penuh  where the entire study populationsampled  amounting to 35 people. The data collection technique using a questionnaire inthe form of statements to measure students' achievement motivation and views ofexpectations for student success and the need for knowledge and skills of students. Theresults showed that the scores of students majoring in fashion class 3  classified asexpectations for success were (34.3%), and the need for knowledge and skills of studentsmajoring in fashion class 3  classified as moderate fashion (45.7%). Of both indicatorsobtained a description for Achievement motivationn of students majoring in fashion class3 is being considered as a whole (34.3%). Keywords:  Achievement Motivation, expectations, Skill and kknowledge